Expanding the horizon for breast cancer screening in India through artificial intelligent technologies -A mini-review - Bhattacharya, Sudip; Varshney, Saurabh; Heidler, Petra; Tripathi, Shailesh K. (Frontiers in Digital Health, 2022)
Introduction Breast cancer is one of the most common cancer among Indian women, with an incidence of 25.8 per 100,000 women according to the Ministry of Health and Family Welfare. Late detection is responsible for poor quality of life (QOL), and it is the leading cause of death. In metropolitan regions, one in every 22 women will have breast cancer over their lifetime; but in rural areas, one in every 60 women will develop breast cancer as per estimates. Aim and objective This paper aims to describe the various AI based breast screening technologies which are used in breast cancer screening in India. Methodology The literature search was done using “Pub Med,” “Google scholar,” and “Scopus” databases for the key terms “technology,” “cancer research,” “artificial intelligence,” “mammography”, “breast cancer,” “cancer,” and/or “neoplasia in breast.” All the relevant articles were included to support this mini review. Results We found that emerging artificial intelligent technologies namely “Niramai”, “iBreastExam,” “MammoAssist” are emerging as an hope for early detection by screening in resource poor settings, in turn, which can improve the QOL among breast cancer patients.